MAKNA ISLAM SEBAGAI AGAMA RAHMATAN LIL ALAMIN PERSPEKTIF PARTAI-PARTAI ISLAM PERIODE 2014-2019 (Studi terhadap Pernyataan Petinggi Partai Islam dalam Menanggapi Isu SARA) - Robiatul Adawiyah (LPPM STAI Muhammadiyah Probolinggo, 2019)
The purpose of this paper is to re-understand the concept of Islam as a religion that rahmatan lil alamin in the perspective of Islamic parties in Indonesia, especially in the period 2014 - 2019. some a priori towards Islam then afraid to study Islam. In the midst of such conditions the term rahmata lil alamin can be an alternative model of Islam that is complained of by many groups. Ironically, this term is interpreted without sufficient scientific basis, it can even be said to have been a meaning bias. By using a socio-anthropolinguistic approach from online-based data, in this paper the authors use a literature study, which is looking for sources of written data that have relevance to the problem being studied. While the data sources that are used both in the form of books, journal articles, magazines and online newspapers are trusted. Based on the study of literature, the data collection techniques both primary and secondary authors use literature techniques and related literature. With this writing the authors hope the concept of Islam rahmatan lil alamin in the perspective of Islamic parties in Indonesia get clarity so that the meaning of Islam rahmatan lil alamin can truly reflect the universal nature and uphold the value of humanity that is fair and civilized and justice for all Indonesian people in particular and all humanity in general